Flow characterization of various singularities in a real-scale ventilation network with rectangular ducts. (15th August 2022) - Malet, J.; Radosavljevic, M.; Mbaye, M.; Costa, D.; Wiese, J.; Gehin, E.
Abstract: Flow characterization in ventilation ducts is important for adequate modeling of contamination transfer. Turbulent flow through straight tubes with circular cross-section has been widely studied, but HVAC networks are quite unlike such ideal cases. Industrial ducts are of large scale, their sections can be rectangular, and they include many singularities (bends, T-junctions, reducers). The objective of this paper is to study the effect of such singularities on the flow in an industrial-scale rectangular ventilation network including over ten vertical and horizontal bends, one T-junction, a ventilation damper, and one section reducer, by performing experimental measurements and numerical simulations. Regarding bend flow, simulations of mean velocity profiles downstream of horizontal and vertical bends are validated on the experimental data. The analysis of the T-junction flow shows that this flow is a mix of bend and straight duct flows and probably depends on the flow distribution in the two inlet branches, as well as on the curvature radius of the T-junction. It is also observed experimentally that a deflector inserted inside a bend strongly impacts the velocity profiles up to 8Dh downstream. Experiments conducted on the impact of leakage in a closed ventilation damper show that this leakage flow cannot be ignored in the simulations. Measurements of the flow downstream of an open ventilation damper show significant variations in concentration homogeneity. These tests form an extensive database for flow measurements at industrial scale, useful for CFD validation, a necessary step before simulating gaseous and particulate flow in ventilation ducts. Highlights: Velocities upstream of singularities are measured in 60 m length ventilation ducts. RSM modelling allows good predictions of the velocities. Impact of a deflector on bend flow shows a velocity decrease downstream. Similarity between bend flow and T-junction flow is shown. Leakage flow of a closed damper cannot be neglected for CFD validations.